The Growth, productivity and nutritional status of Salicornia brachiata Roxb. cultivated in saline soils supplemented with organic manures under sea water irrigation - Ramasubramanian, Arumugam; Uyyavanthan, Kavitha (Journal of Plant Stress Physiology, 2021)
Halophytic crops are being explored for their nutritional, culinary, oilseed, forage/ feed crop, medicinal, and wastewater treatment potential. Along the Palk Bay region, a short term field experiment was conducted at coastal inlands of Kattumavadi village of Puthukottai district, Tamilnadu during the monsoon season of 2017 to evaluate the cultivation potential of Salicornia brachiata Roxb. in coastal sandy loam soil supplemented with different rates of farmyard manure (FYM) and halophytic compost (HC) irrigated with seawater. Observations recorded in the present study clearly indicated that supplemental fertilizers can play a vital role in the restoration of soil fertility, particularly in terms of available nitrogen and organic carbon in saline soils. HC treated plants showed increased biomass production (3240 Kg ha-1) at 60 DAP compared to control and other treatments. The application of FYM @ 2 ton ha-1 and HC @ 1 ton ha-1 significantly enhanced dry matter production and the proximate analysis exhibited less variation in total phenols and ascorbic acid with the increase in the rates of manure applications.